Motivational Factors Influencing Accountancy Students of Aldersgate College to Become Certified Public Accountant - Pumihic, Kcy Faith; Pumihic, Mercedes B.; Leonardo, Thea Rose (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
he study examines the factors influencing students' decisions to pursue accounting certification and their impact on Certified Public Accountant (CPA) qualification. It focuses on academic, financial, social, and career motivations, investigating their relationships with age, gender, and year level. Utilizing the convergent parallel method with a descriptive correlational approach and stratified random sampling, the research was confined to Aldersgate College, Inc. A survey questionnaire was administered to 115 accountancy students across all year levels. The findings suggest several key insights. Firstly, students aged 19-20, predominantly female, and in their first year exhibit a heightened interest in accounting certification. Financial, social, and career motivations emerge as the most influential factors, with academic motivation following closely behind. Secondly, while significant correlations exist between motivational factors and age/gender, their relationship with year level is comparatively weaker. Notably, motivational factors display a positive association with age and gender, indicating their substantial influence. Conversely, the correlation with year level is marginal, suggesting its limited impact. Consequently, age and gender emerge as more salient variables than year level in driving students' motivation towards CPA certification. These findings have important implications for accounting educators, policymakers, and practitioners who can use them to develop more effective strategies to motivate accounting students towards achieving CPA certification and success in their careers.